Respuesta :
Before we begin, you should remember the following exponential rules:
Rule #1: xᵃ * xᵇ = xᵃ⁺ᵇ
Rule #2: (xᵃ)ᵇ = xᵃᵇ
Rule#3: xᵃ / xᵇ = xᵃ⁻ᵇ
Now, for the given problem:
1- If the given problem was:
(c⁶c²)⁵
We will start by simplifying what's inside the brackets.
To do this, we will apply Rule#1 as follows:
(c⁶c²)⁵ = (c⁶⁺²)⁵ = (c⁸)⁵
Now, we can simplify this by applying Rule#2 as follows:
(c⁸)⁵ = c⁸ˣ⁵ = c⁴⁰
2- If the given problem was:
[tex](\frac{c^6}{c^2} )^5[/tex]
We will start by simplifying what's inside the brackets.
To do this, we will apply Rule#3 as follows:
[tex](\frac{c^6}{c^2} )^5 = (c^6^-^2)^5 = (c^4)^5[/tex]
Now, we can simplify this by applying Rule#2 as follows:
(c⁴)⁵ = c⁴ˣ⁵ = c²⁰
Hope this helps :)